Reasons For and Against Giving Money to Charities: A Focus on the French and UK Markets - Stefanini, Camille C (2009)
Charitable giving and donors' behaviour have received extensive attention in past research while the case of non-donors has been highly neglected. As charities need more and more funds to sustain their actions towards the cause they are supporting, they need to find as much resources as they can. However, the charitable market is saturated and faces fierce competition (Eveland and Crutchield, 2007). Besides, with the recent recession, the amount of donors' contributions tends do decrease. It is suggested that there is an opportunity to broaden the market by extending the study of charitable behaviour to non-donors. Based on Westaby's statement (2005a) that reasons are better predictor of behaviour than attitudes, this paper presents the results of a study that examined the reasons for and against giving money to charities within the context of two European countries, the UK and France. It investigated whether the two populations' behaviours differ or common marketing tactics could eventually be developed. Eleven qualitative interviews were carried out in each country with donors and non-donors. The results provide useful background for an extension of the market size and suggest that apart from a strong feeling of guilt among UK citizens, the two nations do not significantly differ regarding their charitable behaviour.